Investigating the Role of Emotional Labor in Service Industry Management: A Qualitative Approach - Ngadi Permana; Muhammad Rizal; Farah Qalbia (LPPM STIE Kasih Bangsa, 2024)
This qualitative study aims to explore the significance of emotional labor in service industry management. Utilizing a phenomenological research model, the investigation delves into the subjective experiences of service industry employees regarding emotional labor. A purposive sampling technique is employed to select participants from diverse service sectors. Data is collected through in-depth interviews and supplemented by observational notes. Thematic analysis is utilized to examine the narratives, identifying patterns and themes related to emotional labor's impact on employee well-being, customer satisfaction, and organizational dynamics. Results reveal the multifaceted nature of emotional labor, highlighting its pivotal role in shaping employee interactions, job satisfaction, and organizational culture within the service industry. Implications for management practices and future research directions are discussed.